Assessment of novel pre-erythrocytic malaria vaccines in humans - Venkatraman, N (2017)
Falciparum malaria remains one of the leading infectious causes of morbidity and mortality worldwide. Though the search for an effective vaccine has seen unprecedented advances in recent years and one of the leading vaccine candidates, RTS,S/AS01 is going to enter pilot deployments in Africa in 2018, there has been no vaccine that has demonstrated durable high level efficacy. This thesis describes four Phase I and Phase II clinical trials assessing novel pre-erythrocytic malaria vaccines in healthy adult UK volunteers. R21 has been developed at the Jenner Institute, University of Oxford. This is an improved RTS,S construct, an antigen derived from the pre-erythrocytic circumsporozoite protein, which is an abundant coat protein involved in sporozoite development and hepatocyte invasion. R21 comprises recombinant particles expressing the central repeat and the C-terminus of the circumsporozoite protein (CSP) fused to the Hepatitis B surface antigen (HBsAg), but without the excess of unfused HBsAg protein found in RTS,S. Both RTS,S and R21 predominantly function by inducing antibodies against the circumsporozoite protein. In addition to humoral immunity, it is widely recognised that T-cell mechanisms are likely to play an important role in malaria immunity and heterologous prime-boost regimes using viral-vectored vaccines have been shown to induce potent T-cell responses. ChAd63-MVA ME-TRAP is a regime that has been developed in the Jenner Institute and the first of the clinical trials described in Chapter 3 assesses the safety and immunogenicity of adjuvanting this regime with a novel saponin-based adjuvant, Matrix-MTM. This trial showed that this regime was safe, well tolerated and did not result in any immunological interference. R21 had never been administered to humans prior to the work described in this thesis. In Chapter 4, I describe two Phase I clinical trials assessing the safety and immunogenicity of R21 given at varying doses administered with two different adjuvants, Matrix-M (MM) and AS01B. Both these trials showed that R21 was safe and well tolerated when administered with either adjuvant and elicited comparable humoral immune responses to RTS,S/AS01B even at one-fifth of the dose (10μg). This formed the basis to test the efficacy of R21/MM, which had a favourable reactogenicity profile, using controlled human malaria infection in malaria-naïve UK volunteers. High level efficacy (> 80%) is reported in Chapter 5 with a three-dose schedule of 10/10/10μg R21/MM given 4 weeks apart. This provides the first evidence of proof-of-concept that this vaccine regime should be tested in malaria-endemic populations.